Re-Desain Masker yang Ergonomis untuk Anak Usia 6-11 Tahun dengan Pendekatan Antropometri - Zetli, Sri; Tarigan, Elsya Paskaria Loyda; Fajrah, Nofriani (SURYA TEKNIKA, 2023)
Despite the significance of mask use, there is still a lack of understanding among Indonesians, with youngsters adhering to the wearing of masks at a rate of 51.6%. The causes include heat, irritability, pain, difficulty breathing, social rejection, and improper mask size and form. One of the ergonomics-related issues is the shape and size of the mask, so one solution is to use anthropometric data while designing the mask. In this study, groups of kids between the ages of 6 and 11 were recruited to redesign masks based on their anthropometric measurements. According to the findings, the distances between the nose's tip and the lower jaw joint (T), the tip of the nose and the rear of the ear bone (U), the nose's distance from the chin (C), and the distance between the eyes and the chin were utilized as anthropometric measurements in the construction of the mask. (B). The mask's size is determined. The mask's length without the strap is 11.16 cm, its length with the strap is 14.53 cm, the central mask's width is 7.02 cm, and the mask's total width is 13.70 cm. The size of the mask from the study and the size of the mask currently on the market differ after measurements were taken into account for anthropometric data